2004
DOI: 10.1038/sj.npp.1300493
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation Increases the Release of Dopamine in the Nucleus Accumbens Shell of Morphine-Sensitized Rats During Abstinence

Abstract: Recent studies in rodents have shown that withdrawal from chronic drug abuse is associated with a significant decrease in dopamine (DA) release in mesolimbic structures, especially in the shell region of the nucleus accumbens. Since the DA system is known to play an important role in reward processes, a withdrawal-associated impairment in mesolimbic DA-mediated transmission could possibly implicate reward deficit and thus enhance vulnerability to drug craving and relapse. We have previously demonstrated that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 59 publications
0
21
1
2
Order By: Relevance
“…In the rat brain, rTMS has been shown to induce signifi cant changes in neuronal circuits evidenced by changes in behaviour and an attenuation of the hypothalamic -pituitary -adrenocortical system (Fleischmann et al, 1995;Keck et al, 2002). Furthermore, it has been demonstrated that rTMS increases dopamine in the dorsal hippocampus (Keck et al, 2002) and the nucleus accumbens (Erhardt et al, 2004;Keck et al, 2002) using microdialysis in rodents. Repetitive TMS in the rat has also been shown to change the expression of proteins refl ected by the synthesis of γ -aminobutyric acid (GABA) by two isoforms of GAD (Trippe et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the rat brain, rTMS has been shown to induce signifi cant changes in neuronal circuits evidenced by changes in behaviour and an attenuation of the hypothalamic -pituitary -adrenocortical system (Fleischmann et al, 1995;Keck et al, 2002). Furthermore, it has been demonstrated that rTMS increases dopamine in the dorsal hippocampus (Keck et al, 2002) and the nucleus accumbens (Erhardt et al, 2004;Keck et al, 2002) using microdialysis in rodents. Repetitive TMS in the rat has also been shown to change the expression of proteins refl ected by the synthesis of γ -aminobutyric acid (GABA) by two isoforms of GAD (Trippe et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Visual determination of the motor threshold in awake animals proved to be reasonably accurate as compared to determination by motor evoked potentials, which was used in other studies (Erhardt et al, 2004;Keck et al, 2002;Müller et al, 2000). Since visual detection of motor threshold was without anesthesia and integrated into the handling procedure, it did not involve additional stress and resembles natural conditions much closer.…”
Section: Discussionmentioning
confidence: 92%
“…In rat microdialysis studies, an increase of dopamine outflow was found with 20 Hz rTMS and a magnetic field strength of 130% of motor threshold (Erhardt et al, 2004;Keck et al, 2002). Besides dopamine outflow, glutamate outflow increased when 2 Hz rTMS was applied with 98% of the maximum stimulator output (Zangen and Hyodo, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…In de rat is gevonden dat TMS bij 2, 20 en 25 Hz de dopamineconcentratie verhoogde in het dorsaal striatum, de nucleus accumbens en de hippocampus (Keck et al, 2000(Keck et al, en 2002Zangen et al, 2002;Kanno et al, 2004;Erhardt et al, 2004). Met behulp van de reeds beschreven techniek raclopride PET en aanverwante SPECT-technieken kan de dopamineafgifte ook worden bestudeerd bij levende dieren en mensen.…”
Section: Tms En Het Beloningssysteemunclassified